Combined value of left ventricular ejection fraction and the Model for End-Stage Liver Disease (MELD) score for predicting mortality in patients with acute coronary syndrome who were undergoing percutaneous coronary intervention - Tuncay Kırıs; Eyüp Avcı; Aykan Çelik (BMC Cardiovascular Disorders, 2018)
Abstract Background The purpose of the study was to investigate whether the addition of left ventricular ejection fraction (LVEF) to the MELD score enhances the prediction of mortality in patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI). Methods This retrospective study analyzed 846 consecutive patients with ACS undergoing PCI who were not receiving previous anticoagulant therapy. The patients were grouped as survivors or non-survivors. The MELD score and LVEF were calculated in all patients. The primary end point was all-cause death during the median follow-up of 28 months. Results During the follow-up, there were 183 deaths (21.6%). MELD score was significantly higher in non-survivors than survivors (10.1 ± 4.4 vs 7.8 ± 2.4, p <  0.001). LVEF was lower in non-survivors compared with survivors (41.3 ± 11.8% vs. 47.5 ± 10.0%, p <  0.001). In multivariate analysis, both MELD score and LVEF were independent predictors of total mortality. (HR: 1.116, 95%CI: 1.069–1.164, p <  0.001; HR: 0.972, 95%CI: 0.958–0.986, p <  0.001, respectively). The addition of LVEF to MELD score was associated with significant improvement in predicting mortality compared with the MELD score alone (AUC:0.733 vs 0.690, p <  0.05). Also, the combining LVEF with MELD score improved the reclassification (NRI:24.6%, p <  0.001) and integrated discrimination (IDI:0.045, p <  0.001) of patients compared with MELD score alone. Conclusions Our study demonstrated that the combining LVEF with MELD score may be useful to predict long-term survival in patients with ACS who were undergoing PCI.